Centro infantil modular y sostenible basado en la cultura montubia y materiales regionales. - Triana Reyes, Roberto Andrés (2025)
The present work proposes the design of a Modular and Sustainable Children's Center based on the montubia culture and the use of materials from the sector, with the objective of improving learning conditions and reinforcing community identity in the Carrasco precinct. Early childhood is a key stage in human development, and in Ecuador, public policies have prioritized the creation of Child Development Centers (CDI) to ensure comprehensive care. However, there are still challenges in terms of infrastructure and the adaptation of these spaces to the cultural particularities of rural communities. The architectural proposal is based on the use of traditional materials such as guadua cane, wood and toquilla straw, taking advantage of their thermal, acoustic and sustainable properties. In addition, the modular design allows for flexibility and efficiency in the distribution of spaces, promoting natural ventilation and lighting. The aim is not only to optimize environmental comfort, but also to strengthen the community's sense of belonging and participation in the construction process.